ANALISIS MODAL TERHADAP SISA HASIL USAHA PADA KOPERASI KREDIT UBEKA ALB. GENTIARAS PRINGSEWU - Yohanes Suharsana; Istiasih Fajar Riani (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
One form is a cooperative venture capital providers. Cooperative capital comes from its owncapital and loan capital. In addition to capital, profit is also one measure of a cooperative survival.Based on this background, the authors are interested in taking the title of Capital Analysis ofCooperative Research Against Business Profits On Credit Cooperatives (KOPDIT) Ubeka. Alb.Gentiaras Pringsewu.This research was conducted at the Cooperative Credit (KOPDIT) Ubeka Alb.Gentiaras Pringsewu, in May and ending in July 2014.Research conducted using quantitative research with data analysis techniques using theirown capital profitability analysis and loan capital to measure the profitability of capital to the balanceof the cooperative. The results of the analysis of the data found that the overall profitability of owncapital amounted to 28.91% while the overall profitability of the loan capital amounted to 6.44%, bothequity and loan capital experienced fluctuating movement. Based on the criteria of health BUMNprofitability of own capital profitability relatively healthy all whereas capital loans classified as lesshealthy. This means that the role given their own capital to increase SHU greater than the loancapital.Based on the results of the study suggested the cooperative needs to promote itself to thepublic and improve the primary savings to get their own capital are more likely to increase the SHU,and use the collector to minimize accounts receivable.